Active-state model of a dopamine D2 receptor-Gαi complex stabilized by aripiprazole-type partial agonists. - Ralf C Kling (Public Library of Science (PLoS), 2014)
Partial agonists exhibit a submaximal capacity to enhance the coupling of one receptor to an intracellular binding partner. Although a multitude of studies have reported different ligand-specific conformations for a given receptor, little is known about the mechanism by which different receptor conformations are connected to the capacity to activate the coupling to G-proteins. We have now performed molecular-dynamics simulations employing our recently described active-state homology model of the dopamine D2 receptor-Gαi protein-complex coupled to the partial agonists aripiprazole and FAUC350, in order to understand the structural determinants of partial agonism better. We have compared our findings with our model of the D2R-Gαi-complex in the presence of the full agonist dopamine. The two partial agonists are capable of inducing different conformations of important structural motifs, including the extracellular loop regions, the binding pocket and, in particular, intracellular G-protein-binding domains. As G-protein-coupling to certain intracellular epitopes of the receptor is considered the key step of allosterically triggered nucleotide-exchange, it is tempting to assume that impaired coupling between the receptor and the G-protein caused by distinct ligand-specific conformations is a major determinant of partial agonist efficacy.